P-215-Quantitative variation of some gut bacteria in Crohn's disease can be related to the patient's gender - Rodrigues, Josias [UNESP]; Santos, Ana Carolina da Silva [UNESP]; Sassaki, Ligia Yukie [UNESP]; Romeiro, Fernando Gomes [UNESP] (Oxford University Press (OUP), 2014)
Background: Imbalance in bacterial species composition of the gut microbiota is one of the factors associated with the cause or complication of the symptoms of Crohn's disease (CD). This disequilibrium consists in the reduction of biodiversity, decrease of genus such as Bifidobacterium and elevation of species such as Escherichia coli. Human microbiota varies among subjects of a same population irrespective of their health condition and among individuals living in distinct geographic locations. In animal models, sex related differences could also be observed in gut bacterial species composition under some pathological conditions. Experiments conducted with mice have demonstrated that the manifestation of type 1 diabetes (T1D) could be under the influence of the animal sex and its serum level of testosterone, which in turn could be modulated by a particular gut microbiota. Considering the existence of similar features between T1D and CD, such as strong genetic component and malfunctioning of the immune system, we investigated whether differences could be observed in the gut microbiota dysbiosis of male and female CD patients. Methods: Fifty and 5 gut mucosal biopsies from 25 adult CD patients (11 males and 14 females) and 43 specimens of an equivalent clinical material from 22 control subjects (11 males and 11 females) were screened for bacterial biodiversity by analyzing sequences of 16SrDNA V6 region. A number of 2-3 samples each from distinct gut segments (from ileum to rectum) were taken from each subject. The 16SrDNA sequences were obtained by sequencing PCR amplicons of the corresponding gene in the Ion torrent PGM sequencer. Identification and classification of the bacterial groups followed the Ribosomal Database Project (RDP) website pipeline. The relationships of the bacterial taxa with each of the study parameters was performed by compiling the data in a MS Excel and the level of statistical significance determined by the Chi-square test. Results: A total of 3203 16SrDNA sequences were detected in the 98 biopsies samples, the majority of which matching Proteobacteria, Firmicutes, Bacterioidetes, and Actinobacteria. The percentage of DNA sequences for each of these phyla found in Male control subjects/Male CD patients was 40.5/33, 32.7/32.4, 20.8/24.5, and 4.4/4,4 for Proteobacteria, Firmicutes, Bacterioidetes, and Actinobacteria, respectively. In Female comparisons, these values were 35.6/42, 39.2/26.3, 19.8/23.3, 5.2/7. Both Male and Female CD patients presented higher numbers of sequences of Actinobacteria and Bacterioidetes than those of control subjects of the same gender. Case-control differences for Firmicutes could be observed only in female comparisons and, for Proteobacteria, although case-control differences were observed in both genders, the nature of difference was distinct, since while in CD female patients a higher number of sequences matching this phylum was detected, in males a reduced number was observed, in comparison with controls. The species responsible for the Proteobacteria variation in both gender was Escherichia coli. Conclusions: The data presented above suggest that any analysis of dysbiosis in CD must take in account the patient's gender, an observation particularly relevant for Escherichia coli, whose association with CD has been most intensively investigated and for which the present study shows a reverse quantitative variation regarding the patients' gender.